EQUITY CROWDFUNDING AS MSME FINANCING ALTERNATIVE TO IMPROVE BUSINESS COMPETITIVENESS IN THE TIME OF COVID-19 (CASE STUDY IN PAK MIN CHICKEN SOP) - WIDAWATI, ETTY; Arifin, Syamsul; anisa, Nur aini (Sekolah tinggi ilmu ekonomi pemuda, 2021)
One indicator of economic growth in a country is inseparable from the existence of Micro, Small and Medium Enterprises (MSMEs) that grow in the midst of society. However, MSMEs often struggle to continue to exist amidst limited capital. What's more, the Covid-19 pandemic that is currently hitting Indonesia has become an obstacle in itself for MSME players. In the era of information technology developments that are running so fast, there are also advances in financial technology that make it easier for MSME players to survive during the Covid-19 pandemic, namely by means of equity crowdfunding. Equity crowdfunding is a crowdfunding service through information technology-based stock offerings. In this study, the authors examined one of the MSMEs engaged in the culinary sector which is currently struggling to increase its competitiveness during the Covid-19 pandemic, namely Sop Ayam Pak Min by using equity crowdfunding on the Santara platform. The purpose of this study was to determine the strategies used by Sop Ayam Pak Min in increasing its competitiveness in the midst of a pandemic and to determine the impact of equity crowdfunding on the business. This research method uses descriptive qualitative approach to literature study and interviews. The result of this research is that equity crowdfunding has an effective role in helping MSMEs Sop AyamPak Min in dealing with the Covid-19 pandemic because the funding allocation obtained can be used wisely and on target.